Assessment of the correlation between the tensile and diametrical compression strengths of 3D-printed denture base resin reinforced with ZrO2 nanoparticles - Al-Sammraaie , Marwa F; Fatalla , Abdalbseet A; Atarchi , Zaid R (Journal of Baghdad College of Dentistry, 2024)
Background: The mechanical properties of 3D-printed denture base resins are crucial factors for determining the quality and performance of dentures inside a patient’s mouth. Tensile strength and diametral compressive strength are two properties that could play significant roles in assessing the suitability of a material. Although they measure different aspects of material behavior, a conceptual link exists between them in terms of overall material strength and resilience. Aim: This study aims to investigate the correlation between tensile strength and diametral compressive strength after incorporating 2% ZrO2 nanoparticles (NPs) by weight into 3D-printed denture base resin. Methods: A total of 40 specimens (20 dumbbell-shaped and 20 disc-shaped) were produced via 3D printing and divided into two groups (n = 10): (1) 3D-printed denture base resin without NPs and (2) the resin was strengthened with 2% by weight ZrO2 NPs. Tensile strength and diametral compressive strength were assessed using a universal testing machine. Results: A detrimental relationship was observed between the tensile strength and diametral compressive strength of 3D-printed denture base resin after the addition of NPs. Conclusion: The enhancement of one property does not necessarily mean the enhancement of another. Caution should be taken to not endanger the quality of a material.